2014
DOI: 10.1166/jnn.2014.9478
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein-Immobilized Polystyrene Nanoparticles Using Impedance Spectroscopy

Abstract: A novel approach for characterization of non-conductive protein-immobilized nanoparticles using AC impedance spectroscopy combined with conductive atomic force microscopy was examined. As AC impedance spectroscopy can provide information on diverse electrical properties such as capacitance and inductance, it is applicable to the characterization of non-conductive substances. Several non-conductive protein-immobilized polystyrene nanoparticles were analyzed using AC impedance spectroscopy, and their impedance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…20 The circuit model shown in Figure 1b was constructed based on the physical characteristics of the electrodes and nanoparticle samples. 13…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The circuit model shown in Figure 1b was constructed based on the physical characteristics of the electrodes and nanoparticle samples. 13…”
Section: Methodsmentioning
confidence: 99%
“…AC impedance spectroscopy combined with a scanning probe microscope (SPM) is useful for investigating the electrical properties of small substances at the nanoscale. In previous studies, SPM-combined impedance spectroscopy was used to determine local electrical properties of thin films, [6][7][8][9][10] identification of biological substance at the nanometer scale, [11][12][13][14] and capacitance imaging of substances with locally different dielectric constants. 15 Results from previous studies showed that SPM-combined impedance spectroscopy would be a promising tool for characterizing non-conductive core-shell nanoparticles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method was exploited to characterize the capacitive properties of a thin inorganic nanoparticle layer or a polymeric thin film. [4][5][6][7] Aside from the studies noted above on non-biological substances, AC impedance spectroscopy is an attractive method for characterizing biological substances because it can collect detailed information on the electrical properties of biomolecules, although this area has been explored only a little. Biological transformations such as DNA hybridization, immunological antibody-antigen interactions, and enzymatic reactions have been clearly indicated by AC impedance spectroscopy, with significant electrical signal changes observed during those biological developments.…”
mentioning
confidence: 99%
“…By varying the protein in the shell layer, the capacitance and inductance were changed such that these electrical properties could be used as tags for protein identification. 5 These studies implied that AC impedance spectroscopy combined with c-AFM is a promising tool for biomolecular characterization that allows the use of only a small amount of biological sample and that both qualitative and quantitative properties of the protein are sensitive to the AC stimuli, resulting in differences in the AC impedance spectroscopy.…”
mentioning
confidence: 99%